PWE-226 Are IBD services up to standard?—results from 1st round of the UK inflammatory bowel disease quality improvement project (IBD QIP). (28th May 2012) - Shaw, I; Fernandez, E; ,
Abstract : Introduction: IBD is a common cause of gastrointestinal morbidity with an estimated 240 000 people affected in the UK. Successive rounds of the UK IBD Audit have shown variation in care and there is a recognised need to implement the National Standards for IBD Care that were published in 2009. The IBD QIP was established as a pilot project to explore the potential of a web based self assessment tool to assist services benchmark themselves against the standards and develop action plans to improve. Methods: The IBD QIP assessment tool was developed through a series of meetings consisting of representatives of key stakeholder groups, including patients. Statements relating to aspects of IBD care were identified from analysis of the Standards and UK audit results. These were then included in a web based tool, similar to the "GRS" used in UK endoscopy. All IBD services in the UK were invited to volunteer for the pilot and after a series of regional meetings, participating sites were provided with access to the tool and asked to complete their assessment and provide feedback on the process. Results were collated centrally and fed back to sites locally. The QIP web site, also included tools for formulating an action plan and a "Shared Document Store" for sites to submit examples of good practice that could be shared with others. Re-assessment is planned for March 2012. Results: 73 sites enrolled for the pilot (64 adult & 9 paediatric services), 62 (85%) of whom submitted data. 52/62 (90%) of sites met to complete the assessment as a multidisciplinary group with at least 2 disciplines represented. 93% of sites took <4 h to complete the rating process. Overall results for all domains showed similar scores for adult and paediatric sites with 18, 17, 23 and 43% of adult and 14, 12, 26 and 48% of paediatric sites scoring A, B, C and D respectively. Representative scores for selected items from adult sites are shown in the following Abstract PWE-226 table 1 (n=56). Conclusion: We have demonstrated that it is feasibile for services to use a web based self assessment tool to benchmark themselves against nationally agreed standards for IBD care. First round results show that the majority of services are currently failing to meet the UK IBD Standards, with two thirds of sites scoring at level C or D. Feedback from the pilot round is currently being used to refine the tool and re-assessment in March 2012 will give sites an indication of their progress. Competing interests: None declared.